(untitled) (Al-Qamar, 2021)
Women play a very important role in human progress and hold an important place in society. The main responsibility of a woman is to protect mankind and the human race. Women at the same time play the role of partner, wife, mother, administrator, teacher, organizer, director, economist, disciplinarian, artist, and queen in the family. This study aims to reveal the efforts of Ūmmahat-ul-Mū’minin for the development of Society. Their life stories motivate and encourage Muslim women to play their significant role in social development. The development of any society is measured by the degree of cultural and social. A society that cares about women and makes them participate in all the things and duties in the society is undoubtedly very advanced. It is concluded that a society that gives women the respect and deals with them as an integrated human, has reached a stage of human awareness. Women have contributed to society’s development and shaped nations’ futures. Women have an important role in a variety of industries in the increasingly complex social landscape. They are no longer merely harbingers of peace, but are increasingly becoming a source of strength and a sign of progress.